A gift from experience: co-production and co-design in stroke and self-management. Issue 1 (2nd January 2019) - Kulnik, Stefan Tino; Pöstges, Heide; Townsend, Rosemary; Micklethwaite, Paul; Jones, Fiona
Abstract: There is increasing emphasis on co-production and co-design of healthcare, for example, the co-design of resources to support people with stroke in self-management. Limited accessibility of materials for people with aphasia (difficulty producing and/or understanding language) is a topical issue. In this paper, we describe our experiences of working with people with stroke and rehabilitation professionals to co-design a resource (book) for stroke self-management support, incorporating accessibility for people with aphasia. In the highly medicalized field of stroke care, rigour is mainly informed by biomedical experimental research paradigms. Interpretations of value are often grounded in assumptions of the biological and social norm. In contrast, our work was guided by 'designerly' conceptualizations of rigour and value. We considered design 'things' (objects/artefacts) versus 'Things' (a forum for people to come together); the book as a boundary object; reciprocity throughout the co-design process; and a pragmatic premise of participatory design. Stroke survivors gifted their stories and experiences to fill the pages of the book. In our work, we have made transparent how we 'do' co-design. We have demonstrated rigour through local accountability. There is value in the book's ability to connect people with stroke and support an encouraging and empowering self-management dialogue.